Peran Unit PPA Polres Payakumbuh dalam Memberikan Perlindungan Terhadap Anak Korban Kekerasan Fisik - Harianja, Marissa; Tenofrimer; Yandriza (Fakultas Hukum Universitas Andalas, 2025)
Children Victims of Physical Violence are children who experience violence with pain, illness or serious injury. In Indonesia, physical violence against children is the second most common form of violence after sexual violence. However, seeing the surge in cases that continue to increase, especially cases of physical violence against children, raises a question regarding the role of this the PPA Unit of the Payakumbuh Police. Therefore, the formulation of the problem that will be discussed in this study is how is the role of the PPA unit of the Payakumbuh Police in providing protection for children victims of physical violence This research uses a sociological juridical method with the nature of descriptive research analysis. The results of the study show that the role of the Payakumbuh Police PPA Unit in an effort to provide protection, namely through mentoring, providing motivation and cooperating with related parties. Assistance to children victims of physical crimes at the Payakumbuh Police has been carried out since the report and/or complaint was received by the PPA Unit. This is mandatory to provide protection for victims both in prevention, mentoring, medical rehabilitation and social rehabilitation efforts which are the rights of children victims of physical violence. The obstacles experienced by this unit are in terms of victims, personnel, facilities, and the Special Service Room. The solution carried out by the Payakumbuh Police is to synergize between PPA personnel and the Payakumbuh Police, approach the victim, provide knowledge to personnel and utilize existing facilities